An improved one-pot synthesis of polydichlorophosphazene from ammonium sulfate and phosphorus pentachloride and assessment of its stability in solution - Yadav, Abhay; Yadav, Prashant; Newale, S. P.; Srivastav, V.; Singh, A. P.; Shanmuganathan, Kadhiravan; Sikder, Nirmala (Journal of Macromolecular Science Part A-Pure and Applied Chemistry, 2025)
Polyphosphazenes, with their synthetic flexibilities, can be tailored to achieve various desirable properties. The synthesis of basic linear polymer polydichlorophosphazene (PDCP) free of branching and crosslinking is the most challenging step, and its extreme sensitivity to moisture makes storage and handling difficult. In the reaction of (NH4)2SO4and PCl5 (1:4.5 mole ratio) via one-pot two-step method, the monomer [Cl3PNP(O)Cl2] synthesized from the 1st step directly undergoes bulk polycondensation (2nd step) to produce PDCP. Due to impurities, the produced PDCP is afflicted by frequent branching, cyclic oligomers, and crosslinking. We are reporting an improved one-pot synthesis coupled with an in-situ purification step of the monomer (as confirmed by 31P NMR) with little excess PCl5 in mole ratio (1:4.6-1:4.8). Further, the stability of PDCP and its solutions in toluene and THF have been examined under an inert atmosphere at three different temperatures: room temperature, 0 degrees C-4 degrees C, and -25 degrees C. These stored samples were monitored for cross-linking, gelling, or any other degradation by characterizing through 31P NMR for the appearance of additional peaks. The PDCP can be stored at -25 degrees C for 2 months (pure) and 4 months (toluene) without any deterioration in its structure.
Keywords: P-trichloro-N-(dichloromonophosphoryl)monophosphazene; Polycondensation; Polydichlorophosphazene; stability in solution; storage life